Understanding Gender Dysphoria from Western and Islamic Perspectives: A Literature Review - El Fuadhilah, Halda Afifa; Hasanudin, Fuat (Direktorat Pondok Pesantren Universitas Islam Indonesia, 2025)
This article discusses gender dysphoria from an Islamic perspective. Gender dysphoria is a gender identity disorder that has been classified in the DSM-V. In Islam, individuals with gender dysphoria should receive interventions so that they can live in accordance with the fitrah (innate disposition) bestowed upon them since birth. This study employs a literature review method, drawing on previous research to explore the definition, impact, and Islamic perspectives on gender dysphoria. The findings indicate that there is no specific Islamic term that directly corresponds to the phenomenon of gender dysphoria. However, several Islamic concepts of gender ambiguity show certain correlations with gender dysphoria. Still, cases of gender dysphoria are more complex than others, as they involve significant psychological aspects. [Artikel ini membahas gender dysphoria dari perspektif Islam dan Barat. Gender dysphoria merupakan gangguan identitas gender yang telah diklasifikasikan dalam DSM-V. Dalam pandangan Islam, individu dengan gender dysphoria perlu mendapatkan intervensi agar dapat menjalani kehidupan sesuai dengan fitrah yang dianugerahkan sejak lahir. Penelitian ini menggunakan metode studi literatur dengan menelaah penelitian-penelitian sebelumnya untuk mengkaji definisi, dampak, serta perspektif Islam terkait gender dysphoria. Hasil penelitian menunjukkan bahwa tidak terdapat istilah khusus dalam Islam yang secara langsung sepadan dengan fenomena gender dysphoria. Namun, beberapa konsep Islam mengenai ambiguitas gender memiliki korelasi dengan kondisi tersebut. Meski demikian, gender dysphoria lebih kompleks karena melibatkan aspek psikologis yang signifikan.]